2018
DOI: 10.1038/s41598-018-23177-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Prediction of Human Prostate Cancer Aggressiveness: Magnetic Resonance Spectroscopy of Histologically Benign Tissue

Abstract: Prostate cancer alters cellular metabolism through events potentially preceding cancer morphological formation. Magnetic resonance spectroscopy (MRS)-based metabolomics of histologically-benign tissues from cancerous prostates can predict disease aggressiveness, offering clinically-translatable prognostic information. This retrospective study of 185 patients (2002-2009) included prostate tissues from prostatectomies (n = 365), benign prostatic hyperplasia (BPH) (n = 15), and biopsy cores from cancer-negative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 49 publications
9
38
0
Order By: Relevance
“…By considering the ensemble of all measurable low molecular weight metabolites in a biological system, many ex vivo metabolomic studies have indicated the greater sensitivity of global metabolite profiles, with or without univariate metabolite analysis, in representing disease status compared with single metabolites . While ex vivo metabolomic evaluations can assist current clinical diagnosis and staging by providing biological information that cannot be obtained by histological evaluation, through the existence of cancer field effects, translating ex vivo findings to in vivo methods is the ultimate aim. A current challenge to this translation is that in vivo MRS studies typically focus on a select few, high‐intensity metabolites, primarily due to resolution constraints.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By considering the ensemble of all measurable low molecular weight metabolites in a biological system, many ex vivo metabolomic studies have indicated the greater sensitivity of global metabolite profiles, with or without univariate metabolite analysis, in representing disease status compared with single metabolites . While ex vivo metabolomic evaluations can assist current clinical diagnosis and staging by providing biological information that cannot be obtained by histological evaluation, through the existence of cancer field effects, translating ex vivo findings to in vivo methods is the ultimate aim. A current challenge to this translation is that in vivo MRS studies typically focus on a select few, high‐intensity metabolites, primarily due to resolution constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature indicated that investigations of human cancer tissue with HRMAS MRS‐based metabolomics have been conducted in many organ systems since 2004, including adrenal, bone, brain, breast, colorectal, esophagus, lung, pancreas, prostate, rectum, skin, stomach, thyroid, etc. Selected papers with sample sizes of 100 or more are summarized in Table .…”
Section: Introduction and Reviewmentioning
confidence: 99%
See 3 more Smart Citations